Identification of an upstream region of the mouse p53 promoter critical for transcriptional expression. - Hale, T K (1995)
We have investigated the transcription factor requirements for basal expression of the mouse p53 promoter by using a combination of reporter and electrophoretic mobility shift assays (EMSAs). We have found that only four regions of the promoter bind transcription factors in EMSAs, suggesting that these are the only important factors for basal transcription. These factors are NF1, USF, ETF-like and a novel factor which we have called PF2. Construction of promoter deletion mutants has shown that the absence of the PF2 site completely inactivates the promoter, whereas deletion of other sites, whilst reducing promoter activity, does not. We suggest that this novel transcription factor (PF2) is critical for expression of the mouse p53 promoter.